Effect of Game-Based Learning with Quizizz on Cognitive Learning Outcomes in Grade IV Mathematics: An Experimental Study - Sani, Nurul Kami; Nurfadilah, Nurfadilah; Zulnuraini, Zulnuraini; Kaharu, Sarintan N; Joni, Ammar Abdullah (FKIP - Universitas Riau, 2025)
This study aims to analyze the effect of implementing the Game-Based Learning (GBL) model assisted by the Quizizz platform on improving students’ cognitive learning outcomes in mathematics. The research was conducted in Grade IV at SD Inpres 2 Besusu using a quantitative approach with a quasi-experimental design and a pretest-posttest method. The evaluation instruments consisted of 12 validated and reliable questions, including 8 multiple-choice items (Cronbach's alpha = 0.772) and 4 essay items (Cronbach's alpha = 0.833). The results showed a significant increase in students' learning outcomes after the application of the GBL model with Quizizz. Paired sample t-test analysis revealed a significant difference between pretest and posttest scores (Sig. 2-tailed = 0.001 < 0.05). The N-Gain score reached an average of 0.6389, which falls into the moderate category. These findings suggest that integrating game elements through Quizizz creates an engaging and interactive learning environment, enhancing students’ understanding of mathematical concepts. The GBL model not only fosters motivation but also directly improves students' cognitive performance. Therefore, the model is recommended as an effective and innovative instructional strategy in primary school mathematics education.